Data Compression Using Stout Codes - Surya Darma Nasution (STMIK Budi Darma, 2019)
The need for data compression is now very important because it is affected by human nature that tends to collect data and also influenced by the need for a process for fast data transfer because the data size becomes smaller. Now many compression algorithms can be used, one of which is the stout codes algorithm. how the stout code algorithm works by encoding characters that often appear with smaller codes than characters with fewer occurrences. The results of data compression in the form of text with the algorithm of the stout code algorithm is the size of the text data becomes smaller with a compression ratio 60% and space saving 40%.